1970
DOI: 10.1099/0022-1317-7-1-55
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Infectious Bovine Rhinotracheitis Virus Multiplication by Thiosemicarbazones

Abstract: SUMMARYThe addition of either isatin-fl-thiosemicarbazone (IBT) or its N-methyl derivative effectively inhibited the multiplication of various isolates of infectious bovine rhinotracheitis virus. Treatment of infected cultures with IBT early or late in the log. phase of replication markedly suppressed the production of infectious virus, indicating that the drug inhibits virus maturation. The time course of formation of infectious virus and of synthesis of viral DNA and viral protein was determined with the inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1971
1971
1991
1991

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…F), the presence or absence of critical concentrations of divalent cations of first transition series metals should be considered as a possible determining factor in the outcome of these experiments. Isatinp-thiosemicarbazone has afforded no protection to mice infected with various ar- Munro and Sabina (1970) RAPP (1964) CAUNT (1967) a RKF=rabbit kidney fibroblast; HTC=human thyroid cells b Thiosemicarbazide used because no suitable vehicle was found for M IBT thropod-transmitted viruses (BAUER 1955;BAUER and SADLER 1960a). Six viruses from the family Togaviridae (PORTERFIELD et al 1978) were screened: one from the genus Alphavirus (Semliki Forest) and the others from the genus Flavivirus (dengue, Ilheus, Nytoya, yellow fever, and Zika).…”
Section: Isatin-p-thiosemicarbazonesmentioning
confidence: 99%
See 1 more Smart Citation
“…F), the presence or absence of critical concentrations of divalent cations of first transition series metals should be considered as a possible determining factor in the outcome of these experiments. Isatinp-thiosemicarbazone has afforded no protection to mice infected with various ar- Munro and Sabina (1970) RAPP (1964) CAUNT (1967) a RKF=rabbit kidney fibroblast; HTC=human thyroid cells b Thiosemicarbazide used because no suitable vehicle was found for M IBT thropod-transmitted viruses (BAUER 1955;BAUER and SADLER 1960a). Six viruses from the family Togaviridae (PORTERFIELD et al 1978) were screened: one from the genus Alphavirus (Semliki Forest) and the others from the genus Flavivirus (dengue, Ilheus, Nytoya, yellow fever, and Zika).…”
Section: Isatin-p-thiosemicarbazonesmentioning
confidence: 99%
“…This observation was confirmed by HERRMANN (1968), using a plaque reduction method relying on diffusion of either IBT or MIBT from an impregnated antibiotic disc. Both CAUNT (1967) and MUNRO and SABINA (1970), using 20 ~M MIBT in liquid tissue culture overlayers, found that the yield of herpes simplex and infectious bovine rhinotracheitis were significantly reduced. Unlike most other studies, IBT appeared to be more effective than MIBT against infectious bovine rhinotracheitis ( MUNRO and SABINA 1970).…”
Section: Isatin-p-thiosemicarbazonesmentioning
confidence: 99%
“…RNA synthesis was studied by the rate of incorporation of 3H-uridine into a perchloric acid precipitable fraction; protein synthesis was determined by the rate of incorporation of 3H-L-leucine into the same fraction (6). Protein content was estimated by the method of Lowry et al (4).…”
Section: Rna and Proteiiz Syrzthesismentioning
confidence: 99%